Study skills of undergraduate public health students during post COVID-19 new normal: Validity and reliability of SSAQ-CCHU instrument - Le, Cua Ngoc; Suwanbamrung, Charuai; Chutipattana, Nirachon; Ayudhaya, Wanvisa Saisanan Na; Rahman, Md. Atiar; Kooltheat, Nateelak; Srisuphanunt, Mayuna (Journal of Posthumanism, 2025)
In the evolving post-COVID-19 educational landscape, this study developed and validated the SSAQ-CCHU, a study skills assessment scale for public health students. Using a cross-sectional design, 302 students participated in exploratory factor analysis (EFA) and 135 in confirmatory factor analysis (CFA). The final scale, comprising three constructs—motivation and attitude, test strategy and comprehension, and processing information—demonstrated strong model fit (χ²/df = 2.45, CFI = 0.92, RMSEA = 0.05) and high internal consistency (Cronbach’s α = 0.88). Significant differences were found in “Processing information” skills across majors (p = 0.016) and in “Motivation and attitude” between genders (p = 0.01). These findings affirm the scale’s validity and reliability, providing a practical tool for educators and policymakers to assess and enhance student study skills in diverse learning environments.